Distraction Osteogenesis for Mandibular Ramus lengthening in Temporomandibular Joint Ankylosis Patients simultaneously with Interposition Gap Arthoplasty - Shahzad Iqbal Malik, Saadia Firdous, Tooba Saeed, Saba Hanif, Hafiz Nasir Mahmood, Kashif Khatak, Sadia Zafar, Sana Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Temporomandibular joint ankylosis is the most common cause of facial deformity.1-4The main etiology of TMJ ankylosis include trauma and infection3,5.TraditionallyTemporomandibular joint Ankylosis patients had been managed with different treatment options including Gap arthoplasty6,Interpositiongap arthroplasty ,distraction osteogenesis and total joint replacement.To prevent reankylosis interposition of fascia or muscle had been documented and if reconstruction of the joint was needed Alloplastic(sialistic)or Autogenous graft ( Costochondral bone graft) had been used.6, 7,8,9 Costochondral graft is preferred for reconstruction because morphological it is similar to the condyle of mandibleandhas agrowth capacity.9But thisgraft is unpredictable in nature and different results are reported and documented including facial asymmetry, over growth, graft resorption, graft failure and even reankylosis.9 Distraction osteogenesis is a recent treatment method for the correction of hypo plastic mandible in Temporomandibular joint ankylosis patients. By using distraction osteogenesislarge skeletal movements are possible with little or no relapse commonly seen in other orthognathic corrections. In this study of 30 patients all patients were treated with TMJ Interposition gap arthoplasty (interposition of temporalis fascia) followed by the application of distractors at ramus of mandible. Mean age was14.96±4.17 years. Patient’s minimum and maximum age was 8 and 24 years respectively. Gender distribution shows that 15(50%) of the patients were male and 15(50%) were females. Male to female ratio was 1:1.Mean ramus length before distraction was 38.70±7.28 mm with 28-52 mm range. Mean ramus length after distraction osteogenesis was 49.00±8.01 mm. Mean increase in vertical ramus length was 10.26±2.86 mm. Minimum increase was 5mm and maximum increase in vertical ramus length was 15 mm respectively. In this study we were able to achieve increase in ramus length in all patient and only patient require reoperation due to failure of distractor appliance which was replaced successfully.